Characterization of variant strains of respiratory adenoviruses isolated in Egypt from 2003 to 2010 - Demian, Pola Nashdy (AUC Knowledge Fountain, 2011)
Human adenovirus (HAdV) has been associated with acute respiratory disease (ARD) in adult and pediatric patients in Egypt. Worldwide, adenovirus of species B, C, and E are predominantly associated with ARD. As part of an influenza-like illness (ILI) surveillance program in Egypt, we isolated 99 adenoviruses from 2003 to 2010. Initial identification of the isolates was accomplished with immunofluorescence assays (IFAs) and then confirmed with multiplex and monoplex PCR protocols. Of the 99 isolates, 39 were species B, 54 were species C, and 1 was species E. Additionally, 5 isolates represented co-infections of both HAdV-B and HAdV-C. Molecular typing by PCR and sequencing of the hexon gene allowed the identification of the serotypes of the HAdV-B isolates as follows: 17 isolates were Ad-3, 14 were Ad-7, 8 were Ad-11a. For the species C HAdV, 19 isolates were Ad-1, nine were Ad-2, 13 were Ad-5 and 12 were Ad-6. One sample in this group also represented a co-infection of Ad-5/Ad-6. The serotypes of the five HAdV-B/HAdV-C co-infections were Ads (3+1) for three cases, while the other two were Ads (3+5) and Ads (3+2). In contrast to previous studies in Egypt, we observed a higher number of HAdV-Cs which was recovered largely from a pediatric population. To reveal any recombination events in the AdV-C species isolates, we sequenced the fibre and the HVR-7 of the hexon genes and detected an Ad-2/Ad-6 recombination. The isolates which showed recombination events had the fibre of Ad-6 and the HVR-7 of Ad-2. For the HAdV-C fibre genes sequenced, the tail region was highly conserved (100% homology of amino acids) whereas the shaft and knob regions showed a high degree of heterogeneity at the nucleotide and amino acids levels. Additional studies are currently underway to determine novel markers of antiviral resistance, and to define possible vaccine candidate components that would be effective for the region.